Pendampingan Usaha Pembibitan Ayam Pelung Rumahan di Kabupaten Pekalongan - Maksum, Fitri Kurniawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
As one of the areas in Bojong District, Pekalongan Regency, Ketitang Kidul Village has residents whose main livelihoods are brick makers, garment workers, traders, livestock breeders, and home-based entrepreneurs engaged in both clothing and food sectors. As in many rural areas, the main issue in this village is the low level of formal education. Limited education and literacy have become contributing factors to various social problems, one of which is poorly managed small-scale businesses that result in suboptimal outcomes. For instance, poultry and dove farming are often considered only as side activities, even though they have great potential to improve the community’s economy if managed properly. Therefore, concrete efforts are needed to empower the existing local resources. This community empowerment program aims to build awareness and provide education on breeding and developing Ayam Pelung (Pelung chicken) as a means to improve family income. Through this community service activity, it is expected that residents can optimize poultry farming while enhancing their household economy. The mentoring process includes training on breeding, maintenance, care, and marketing strategies. As a result of this empowerment program, the community has begun to independently breed and develop Ayam Pelung farming businesses, successfully marketing them at competitive prices and gaining additional income for their families